Perceived Barriers and Preventive Measures of COVID-19 Among Healthcare Providers in Debretabor, North Central Ethiopia, 2020 - Birihane BM; Bayih WA; Alemu AY; Belay DM (Dove Medical Press, 2020)
Binyam Minuye Birihane, Wubet Alebachew Bayih, Abebaw Yeshambel Alemu, Demeke Mesfin Belay College Health Sciences, Debretabor University, Debretabor, EthiopiaCorrespondence: Binyam Minuye Birihane Tel +251 921574025Email biniamminuye@yahoo.comBackground: Healthcare professionals are at the frontline facing the pandemic. Since the pandemic is new with sophisticated needs of resources, identifying perceived barriers of the healthcare institutions has an important input for the government in slowing the viral spread and prevents healthcare professionals from infection.Objective: The study was aimed to assessperceived barriers and preventive measures of corona virus disease among healthcare providers in Debretabor Town, north central Ethiopia.Methods: An institution-based cross-sectional survey was conducted among healthcare providers working in Debretabor town, north central Ethiopia from May 1 to 15, 2020. Data were collected using a self-administered questionnaire. Data were coded, entered, cleaned, and checked using Epi data statistical software version 4.2.0.0 and analysis using STATA Version 14 statistical software. Descriptive statistics of different variables were presented in figures, text, and tables. Chi-square (chi2) test of independence was considered to examine the nonparametric association of factors with preventive practice, and association was considered at a P-value of less than 0.05.Results: A total of 183 healthcare providers participated in the survey, of which 67.76% were males, and 80.87% were in the age range of 25– 35 years. About 45% of participants were nurses. In the current study, overall preventive practice was 68.3%. Despite recommendations by the World Health Organization, avoidance of outdoor, physical distancing, and avoiding meeting a person with a coughwere not implemented by 32.24%, 24.18%, and 13.11% of healthcare providers, respectively. Insufficient training, lack of policy, less commitment to infection control, and limitations of resources were perceived as major barriers for practicing preventive measures during the pandemic.Conclusion: Preventive measures taken by healthcare providers were poor. Multiple barriers, such as insufficient training related to the pandemic, limitation of resources, and less commitment of healthcare providers to infection prevention measures were reported. So, the government should work on reducing the pandemic propagation by fulfilling the barriers using different means or strategies.Keywords: COVID-19, barriers, preventive practice, Ethiopia, health care providers